X-ray absorption spectroscopy and neutron-diffraction study of persistent luminescent Sr2MgSi2O7 glass-ceramics. (15th August 2021) - Fernández-Rodríguez, L.; Gorni, G.; Mather, G.C.; Savvin, S.; Cuello, G.J.; Durán, A.; Pascual, M.J.
Abstract: Glass-ceramics based on the Eu2 O3 /Dy2 O3 -doped Sr2 MgSi2 O7 phosphor have been obtained from sintering and crystallization of glass powders. The doped parent glasses show red emission under excitation of UV light. After thermal treatment, the corresponding glass-ceramics show persistent blue emission which emanates from Eu 2+ incorporated in the crystals; red emission also occurs from Eu 3+ in the residual vitreous phase. The aim of this work is to investigate the structure of defects such as oxygen and strontium vacancies in the Sr2 MgSi2 O7 crystals and the environment, oxidation state and coordination of the Eu and Dy ions in the glass-ceramics, their partitioning between crystalline and glassy phase and their influence on luminescence properties, employing X-ray absorption spectroscopy (XAS) and neutron diffraction (ND) as investigative structural tools. We suggest that the luminescence mechanism involves the presence of shallow electron traps that are abruptly emptied for temperatures above 100 K. The most persistent luminescence is likely due to an effective concentration of Eu 2+ in the dendritic-shaped crystals in one of the particular compositions, and with a suitable level of Sr vacancies, even though Sr vacancies are most likely formed in all the investigated samples. Graphical abstract: Image, graphical abstract